Learning from Debaters: Insights Into Their Learning Strategies - Fitri Alfia Rahmawati; Johannes Ananto Prayogo; Furaidah Furaidah (Graduate School of Universitas Negeri Malang, 2020)
Abstract: This study aims to analyze English debaters’ learning strategies in improving their debate skills. The researcher used descriptive qualitative in the form of in depth interview in which three successful English debaters were involved in this study. The result reveals that debaters habituate themselves to read a lot, watch debate videos and practice by using a wide variety of language learning strategies. Those strategies are seeking practice opportunity, using resources, overviewing materials, asking for correction, using synonym or circumlocution, self-evaluating, practicing naturalistically, taking note, summarizing, using progressive relaxation, deep breathing or meditation and cooperation with peers.Abstrak: Penelitian ini bertujuan untuk menganalisa strategi belajar para ahli debat bahasa Inggris dalam mengembangkan kemampuan debatnya. Dalam penelitian ini, peneliti menggunakan pendekatan deskriptif kualitatif dalam bentuk interview mendalam dengan melibatkan tiga ahli debat yang sukses. Hasil penelitian ini mengungkapkan bahwa para ahli debat membiasakan diri untuk banyak membaca, menonton video debat dan berlatih dengan menggunakan berbagai macam strategi pembelajaran bahasa. Strategi-strategi tersebut adalah mencari peluang untuk praktek, menggunakan sumber belajar, meninjau materi, meminta koreksi, menggunakan sinonim, mengevaluasi diri, berlatih secara natural, mencatat, meringkas, menggunakan relaksasi progresif, pernapasan dalam atau meditasi dan kerja sama dengan teman sebaya.